A CRITICAL DISCOURSE ANALYSIS OF A VINTAGE AMERICAN AIRLINES ADVERTISEMENT - Nathan John Dover (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
Critical Discourse Analysis (CDA) is a rapidly increasing area of study used by Applied Linguists to examine discourse, that is spoken or written communication, found in areas such as education, media and politics. CDA studies focus on the relationship between society and discourse and how the use of language reinforces already established societal roles. This paper focused on a vintage American Airlines advertisement of 1968 which is a classic example of utilitarian advertising that purported a false reality of air travel in the late 20th century. Using the three-dimensional CDA framework designed by Fairclough (1989) the results showed a manipulation of gender roles by the advertisers intended to appeal to the male dominated passengers of the airline. Primarily, the alignment of air hostess with that of a mother. The maternalisation of this profession reflected the advertisers’ views of the time and in a wider societal perspective, power inequalities between men and women.